Phenomenology Study: Trigger Factors of Fraud Tendency on Accounting-Finance Division (Jurnal Dinamika Akuntansi, 2016)
This study aims to examine the factors that influence the possibility of fraud on the division of accounting-finance. The population in this study were lecturers and staff at the Faculty of Economics, Semarang State University who engaged in the activity of accountability report (SPJ). The number of samples was 15 respondents by applying proportional cluster sampling, this study used qualitative method namely phenomenology and applied descriptive analysis in order to obtain comprehensive results. The results showed that rationalization factors affecting the possibility of fraud. Furthermore, capability factor also gave effect to the possibility of fraud.